A syntactical analysis of the potential form (kanoukei) in the Japanese language - Taulia; Yusuf, Muhammad; Mipo; Gani, Petrus (Abdul Media Literasi, 2025)
This study presents a comprehensive syntactical analysis of the potential form (Kanoukei) in Japanese, examining its structural patterns and pedagogical implications. The research employed a qualitative, library-based methodology to systematically analyze conjugation rules and syntactic structures across different verb groups and sentence types. The findings reveal that Kanoukei follows predictable patterns: godan doushi undergoes phonological changes (-u to -eru), ichidan doushi adds -rareru, and fukisoku doushi demonstrates irregular but consistent forms. Crucially, the study identifies the obligatory particle shift from を (o) to が (ga) as a fundamental syntactical restructuring that signifies a cognitive shift from action-oriented to capability-focused expressions. The analysis supports Shibatani's (1990) theoretical framework regarding the historical evolution of Kanoukei from passive constructions, explaining its unique grammatical position that bridges voice modification and modality expression. The research demonstrates Kanoukei's consistent implementation across affirmative, negative, and interrogative sentence structures, confirming its grammatical stability in Japanese syntax. From a pedagogical perspective, the study provides a structured framework for teaching Kanoukei, which is particularly beneficial for Indonesian learners who face challenges due to linguistic differences between Japanese and their native language. The findings provide educators with evidence-based strategies for transforming Kanoukei instruction from rote memorization to conceptual understanding, potentially reducing common errors and enhancing learning outcomes. This research makes a significant contribution to Japanese language pedagogy while establishing a replicable methodology for analyzing other complex grammatical structures.